2015
DOI: 10.15578/squalen.v10i1.132
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Biodegradability of Acid-soluble Chitosan-Starch Based Film

Abstract: Chitosan-starch blend film showed desirable elongation and oxygen transmission rate (OTR) values and demonstrated rapid degradation in soil burial treatment. The incorporation of higher glycerol concentration lowered tensile strength but increased the amount of transmittable water vapour. The biodegradability of chitosan-starch based film was tested using soil burial test. Chitosan-starch blend films were able to degrade naturally at slightly similar period, ranging from 72–87 days. The addition of glycerol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In fact, Halim et al [56] reported that chitosan with high molecular weight has reduced biodegradation whereas, with low molecular weight, biodegradation rate is enhanced. Besides that, Rachmawati et al [57] showed that chitosan film degrades naturally in soil in a period ranging from 72–87 days.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Halim et al [56] reported that chitosan with high molecular weight has reduced biodegradation whereas, with low molecular weight, biodegradation rate is enhanced. Besides that, Rachmawati et al [57] showed that chitosan film degrades naturally in soil in a period ranging from 72–87 days.…”
Section: Resultsmentioning
confidence: 99%
“…The soil color likewise changed from brown to a form of blackish tone as time went on, and the film deteriorated. This supports the formation of humus and microbial degradation . Kabir and co-workers also declared that microbial degradation alters the strength and color of polymeric material …”
Section: Resultsmentioning
confidence: 65%
“…This supports the formation of humus and microbial degradation. 70 Kabir and co-workers also declared that microbial degradation alters the strength and color of polymeric material. 67 …”
Section: Resultsmentioning
confidence: 99%
“…The development and application of biodegradable starch-based materials have attracted increasing attention due to the well-recognized issues of oil shortage and the growing interest in easing the environmental burden due to extensive use of petrochemically-derived polymers. Twelve Andean crops (tubers, legumes, roots, and fruits) were used for manufacturing starch films [141]. The authors used the cellulose film as the control one.…”
Section: Biodegradabilitymentioning
confidence: 99%